Biodegradation of Navy N5RL1 carpet dye by Staphylococcus saprophyticus strain BHUSS X3 - Kumari L.; Verma A.K.; Tiwary D.; Giri D.D.; Nath G.; Mishra P.K. (My University, 2025)
Biodegradation of Navy N5RL1, a widely used acidic azo dye in carpet industry, was studied by bacterial strain isolated from the dye-contaminated soil collected from a carpet industry premises located in Bhadohi, Sant Ravidas Nagar and Uttar Pradesh, India. The isolated strain was identified as Staphylococcus saprophyticus BHUSS X3 on the basis of morphological, biochemical and 16S rRNA gene sequencing analysis. The strain BHUSS X3 decolorized 95.7 % of dye (100 mg/l) within 6 h at optimum pH 8, temperature 35 °C, inoculum 4.0 % under static condition during 24 h incubation. The isolated bacterial strain BHUSS X3 can toralate dye concentration upto 1,000 mg/l. The dye degradation metabolites were confirmed by analysis of degraded products using UV–Vis spectrophotometric, HPLC and FTIR technique. The phytotoxicity analysis was also conducted on Phaseolus aureus and enhanced seed germination was recorded. © 2015, The Author(s).